2010
DOI: 10.1111/j.1530-0277.2010.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Hyperlipidemia and Vitamin E Status in Response to Chronic Alcohol Self-Administration in Cynomolgus Monkeys

Abstract: Background Chronic ethanol self-administration induces oxidative stress and exacerbates lipid peroxidation. α-Tocopherol is a potent lipid antioxidant and vitamin that is dependent upon lipoprotein transport for tissue delivery. Methods To evaluate the extent to which vitamin E status is deranged by excessive alcohol consumption, monkeys voluntarily drinking ethanol (1.36 to 3.98 g/kg/day for 19 months, n=11) were compared with non-drinkers (n=5, control) Results Three alcohol drinking animals developed hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…This may be due to the increased activity of HMG CoA reductase, an enzyme involved in the rate-limiting step of cholesterol biosynthesis during alcohol ingestion. This is in line with previous studies [1,34,35]. Cholesterol is a known precursor of the male hormone, testosterone, which is utilized by germ cells and is required mainly to organize the lipid bilayer of the sperm plasma membrane [36].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This may be due to the increased activity of HMG CoA reductase, an enzyme involved in the rate-limiting step of cholesterol biosynthesis during alcohol ingestion. This is in line with previous studies [1,34,35]. Cholesterol is a known precursor of the male hormone, testosterone, which is utilized by germ cells and is required mainly to organize the lipid bilayer of the sperm plasma membrane [36].…”
Section: Resultssupporting
confidence: 81%
“…Testicular lipids consist of glycerides, which form the energy source of germ cells, and sterols and phospholipids, which are the primary structural components of membranes and cholesterol, which serve as the precursor for testicular steroidogenesis [31]. Chronic alcohol intake is known to cause hyperlipidemia both in man and animals [1]. Consistent with this observation, our study also showed that excessive alcohol et al [42] and Awano et al [43] reported that phospholipids serve as substrates for spermatozoa during their development and maturation; therefore, the rise in total testicular phospholipids in alcohol-treated animals observed in this study could be due to a decreased rate of utilization of these compounds as a result of germinal cell depletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic alcohol intakes also result in adverse physiological consequences to the liver, heart, blood, and brain (Carden et al , 2006; Hemby et al , 2006; Walker and Grant, 2006; Freeman et al , 2006; Ivester et al , 2007; Acosta et al , 2010; Cheng et al , 2010; Freeman et al , 2010; Lebold et al , 2011). However, the effects of a multi-year protocol of EtOH self-administration with repeated abstinence have not been reported, and we hypothesized that adaptations in aspects of striatal function likely contributes to stereotyped heavy drinking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…While there is growing evidence for a role of RBP4 expression in obesity-induced diabetes (Yang et al, 2005), no previous data regarding circulating levels of RBP4 with excessive alcohol intake is present in the literature. However, a relationship between vitamin homeostasis and regulation of lipid levels with excessive alcohol intake has been observed in this non-human primate model and may integrate the roles of vitamin status, lipoprotein levels, and inflammatory processes in alcohol related pathology (Lebold et al, 2010). Like ITIH4, the changes in RBP4 levels observed in monkeys were not evident in the human subjects examined.…”
Section: Discussionmentioning
confidence: 96%